Magnetic microboats for floating, stiffness tunable, air–liquid interface epithelial cultures. Issue 17 (23rd July 2019) - Chandrasekaran, Arvind; Kouthouridis, Sonya; Lee, Wontae; Lin, Nicholas; Ma, Zhenwei; Turner, Mark J.; Hanrahan, John W.; Moraes, Christopher
Abstract : Magnetically anchored microboats that can reliably and rapidly create air–liquid interface culture conditions in substrate-stiffness tunable epithelial cell cultures. Abstract : To study respiratory diseases, in vitro airway epithelial models are commonly implemented by culturing airway cells on a porous surface at an air–liquid interface (ALI). However, these surfaces are often supraphysiologically stiff, which is known to affect the organization, maturation, and responses of cells to potential therapies in other biological culture models. While it is possible to culture cells on soft hydrogel substrates at an air–liquid interface, these techniques are challenging to implement particularly in high-throughput applications which require robust and repetitive material handling procedures. To address these two limitations and characterize epithelial cultures on substrates of varying stiffness at the ALI, we developed a novel "lung-on-a-boat", in which stiffness-tuneable hydrogels are integrated into the bottoms of polymeric microstructures, which normally float at the air–liquid interface. An embedded magnetic material can be used to sink the boat on demand when a magnetic field is applied, enabling reliable transition between submerged and ALI culture. In this work, we prototype a functional ALI microboat platform, with integrated stiffness-tunable polyacrylamide hydrogel surfaces, and validate the use of this technology with a model epithelial cell line. We verify sufficient transport through the hydrogel base to maintain cell viability and stimulate cultures, using a model nanoparticle with known toxicity. We then demonstrate significant morphological and functional effects on epithelial barrier formation, suggesting that substrate stiffness is an important parameter to consider in the design of in vitro epithelial ALI models for drug discovery and fundamental research.